Rational Expectations Models with Anticipated Shocks and Optimal Policy - Roland Winkler; Hans-Werner Wohltmann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
This paper investigates optimal policy in the presence of anticipated (or news) shocks. We determine the optimal unrestricted and restricted policy response in a general rational expectations model and show that, if shocks are news shocks, the optimal unrestricted control rule under commitment contains a forward-looking element. As an example, we lay out a micro-founded hybrid New Keynesian model and show i) that anticipated cost-push shocks entail higher welfare losses than unanticipated shocks of equal size and ii) that the inclusion of forward-looking elements enhances distinctly the performance of simple optimized interest rate rules.
Keywords: E52; E32; C61; 330